Unilocular and multilocular thymic cysts: A study on the possible histomorphological and/or clinical differences - BOZKURTLAR, EMİNE (My University, 2022)
Objective: Thymic cysts are rare mediastinal cystic pathologies and have two subtypes namely unilocular and multilocular. This study aims to investigate the clinicopathological characteristics of thymic cysts and to compare the clinical and histopathologic features of multilocular thymic cysts (MTCs) and unilocular thymic cysts (UTCs).
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Thymus; Cyst; Multilocular; Unilocular; Pathology; Histomorphology